A comparative study on the learning processes of primary school and university students - Gümüşay, Zülal (My University, 1999)
Bu çalışmada, dil öğretiminin bazı yönleri ve öğretmen-öğrenci etkileşimi incelenmiş, bir dilin başarılı öğrenilmesine etki ettiği düşünülen çeşitli kavramlar değerlendirilmiştir. İkinci dil sınıflarında amaçlanan, etkili ve verimli dil öğrenim ortamı oluşturmaktır. Öğrenme süreci, bilinçli öğrenme stratejilerini ve tekniklerini kapsadığından, öncelikli amacımız bu stratejilerin, öğrenme yöntemlerinin ve öğrenme sürecinde varolan zihinsel işlemlerin kullanımı artırmaktır. Öğretimin amacı, öğrencilerin potansiyellerini artırmaktır. İkinci bir dili öğrenen öğrenci, 'iyi' bir insan olma yolundadır. 'İyi' kavramı, bireyin kendisi ve diğer insanlarla olan ilişkisi hakkında daha fazla bilgiye sahip olmasına karşılık gelir. Başka bir dili bilme; bir iş sahibi olmasını, kişisel fikirlerin ve inançların ifade edilmesini, daha iyi bir eğitim alabilme gibi bazı faydalar sağlar. Son zamanlarda, dil öğrenimi ve öğretimi, milyonlarca insanın günlük yaşantısında öncelikli olmaya başlamıştır. Bu yüzden dil öğretmenleri, öğrencilerin ikinci dile ait gereksinimlerini karşılamalıdır. Bu çalışmada; öğretme sürecine öğrencilerin temel ihtiyaçlarına hizmet eden ve bu sreci daha anlaşılır kılan bir görüşle yaklaşarak; öğrenciler, ikinci dillerini, uygulamalı bağlamların yer aldığı iyi düzenlenmiş

derslerinde kullanmaları konusunda harekete geçirilmişlerdir. Yaş, sınıf ortamı türü, sunulan dil bilgisinin türü ve bireysel farklılıklar gibi etmenler incelenerek kişisel yetenekler değerlendirilmiştir. İkinci dil öğrenimindeki karmaşıkların bazılarını göstererek, ikinci dil sınıflarında başarılı ve amaca yönelik öğrenme-öğretme ortamına önderlik edecek bazı seçenekler önerilmiştir. ABSTRACT A second language class consisting of both good and poor learners can not create the same learning environment for both. For this reason, an second language teacher should ask these questions: 1. What kind of interaction can be observed between teacher and good student, and teacher and poor student ? How do different students perceive the goals of classroom activities and classroom interaction ? Trying to answer these questions, what has been aimed in second language classrooms has been to create an affective and fruitful language learning environment. In this study, some aspects of teaching and also the interaction of teacher and learner have been examined and various concepts to be thought to contribute to the successful learning of a language have been evaluated. Since the learning process includes conscious learning strategies and techniques, our primary is to promote a high level of proficiency in a second language by increasing learning outcome strategies, techniques and mental processes. The goal of teaching is to develop the students' potential. The student learning a second language becomes a 'better' person. The concept of 'better' refers to greater insight into one's self and one's relation ship with others. Knowing another language embodies a variety of advantages: getting a job, the expression of personal opinions and beliefs, a chance to get educated, career. Recently, language learning and language teaching have been primary to the everyday lives of millions. Teachers of languages must get on with meeting the needs of their students. In this study, considering teaching from a second language learning perspective in a way which serves the unique needs of actual students and which leads to a more comprehensive and scientifically-based view of language teaching, the students have been motivated to use their second language in purposeful contexts in well-organised English classes. Examining a variety of differences such as age, type of classroom environment, type of language input, and individual differences, individual performances have been evaluated. In this study, some of complexities in second language learning have been illustrated and some alternative methods which may lead to successful and purposeful learning-teaching environment in second language classrooms have been proposed.
Keywords: Dil; İngiliz dili_Eğitim ve öğretim; İngilizce; Uygulamalı dilbilim